2014
DOI: 10.1155/2014/870193
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Level of Maxillary Sinus and Cortical Bone Thickness at Maxillary Posterior Quadrant, in Three Different Growth Patterns: 3D-Computed Tomographic Study

Abstract: Objective of this retrospective study was to measure cortical bone thickness and lowest level of maxillary sinus at maxillary posterior quadrant in different growth pattern (hypodivergent, average, and hyperdivergent) at prospective microimplant placement sites in order to understand both safety and stability aspects of microimplant placement by using cone-beam 3-dimensional computed tomographic images. In posterior quadrant, vertical distance from cementoenamel junction to lowest level of maxillary sinus at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In confirmation with our study results, previously only one study has been reported in literature stating hypodivergent growth pattern shows reduced basal bone width and needs more horizontal insertion or reduced length of the implant due to proximity to the sinus floor. 24 Further in our study, when the mean A-P depth and mean M-D width was compared among the 3 study groups, Group-2 had the longest mean A-P depth and longest mean M-D width of the maxillary sinus, whereas Group-1 had the shortest mean A-P depth and mean M-D width. Mean maxillary sinus volume was statistically significantly less in Group-1 when compared to other groups.…”
Section: Discussionmentioning
confidence: 47%
“…In confirmation with our study results, previously only one study has been reported in literature stating hypodivergent growth pattern shows reduced basal bone width and needs more horizontal insertion or reduced length of the implant due to proximity to the sinus floor. 24 Further in our study, when the mean A-P depth and mean M-D width was compared among the 3 study groups, Group-2 had the longest mean A-P depth and longest mean M-D width of the maxillary sinus, whereas Group-1 had the shortest mean A-P depth and mean M-D width. Mean maxillary sinus volume was statistically significantly less in Group-1 when compared to other groups.…”
Section: Discussionmentioning
confidence: 47%
“…Vibhute PJ et al, measured the thickness of cortical bone using computed tomography and found out that the cortical bone thickness is increased at the sinus floor level and above it than below the sinus floor. 18 The safer zone for placement of the implant concerning maxillary sinus level varies in different growth patterns, as was the finding of Vibhute PJ et al…”
Section: Discussionmentioning
confidence: 92%
“…In confirmation with our study results, previously only one study has been reported in literature stating hypodivergent growth pattern shows reduced basal bone width and needs more horizontal insertion or reduced length of the implant due to proximity to the sinus floor. 24 …”
Section: Discussionmentioning
confidence: 99%